2002
DOI: 10.1309/w00t-2ca8-mh68-rvdv
|View full text |Cite
|
Sign up to set email alerts
|

Telepathology for Routine Light Microscopic and Frozen Section Diagnosis

Abstract: Telepathology (TP) uses telecommunication linkages to electronically capture, store, retrieve, and transmit images to distant sites. We assessed the feasibility of a dynamic real-time TP system for light microscopic (LM) diagnosis of anatomic pathology specimens, including frozen sections. Six pathologists, in 2 separate periods, read a set of 160 retrospectively retrieved slides (80 of which were frozen sections) by TP and LM. Reading times were recorded. Diagnoses were compared with the reference diagnosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…It was originally described in the late 1990's[12] and early 2000's. [345678] Of the studies that have been published, several relate to neuropathology[491011] or to cytologic preparations[8121314] comparable to intraoperative touch preparations (ITPs).…”
Section: Introductionmentioning
confidence: 99%
“…It was originally described in the late 1990's[12] and early 2000's. [345678] Of the studies that have been published, several relate to neuropathology[491011] or to cytologic preparations[8121314] comparable to intraoperative touch preparations (ITPs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the time span required to make a diagnosis is another important thing that should be considered in an urgent task, the intraoperative frozen section. The mean reported time span ranged from 3 to 14.2 minutes [16,[19][20][21]. The average time span of our system was only 4.5 minutes.…”
Section: Discussionmentioning
confidence: 93%
“…However, no negative major impact occurred in these 2 cases as a result of teleconsultation. The time span of telepathology (mean ± SD [range], 4.5 ± 2.8 minutes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]) is rather short compared with routine intradepartmental consultation (getting from the main building of the hospital to the operating room and making the diagnosis, 18.6 ± 4.1 minutes [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]). Cases that took longer were mainly the result of diagnostic problems.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Most studies focusing on intraoperative and fine needle aspiration consultations have shown that the accuracy of telepathology is comparable to conventional in-house methods, though the time required for such diagnoses is usually longer and the deferral rate is sometimes slightly higher. [12][13][14][15][16][17][18][19][20][21][22][23] This technology is particularly useful in certain settings, including transplant pathology, dermatopathology, and neuropathology, where the cases handled are often fundamentally different from general surgical pathology and where on-site subspecialtytrained pathologists are scarce. 20,[24][25][26][27][28][29][30][31][32] Most of the early systems delivered a series of static images over a dedicated ISDN (Integrated Services Digital Network) connection or the Internet, and were shown to be adequate for routine use.…”
Section: Introductionmentioning
confidence: 99%